Peptidoma parcial do veneno do escorpiao da amazonia Brotheas amazonicus - Ivanildce Cristiane Ireno (2009)
Brotheas amazonicus is an endemic scorpion from the northern Brazil. Since it dwells the Amazon forest, human accidents involving this species occur sporadically. In this study, two-dimensional liquid chromatography (2D-LC), MALDI-TOF-TOF, de novo sequencing and similarities searches were employed in assessment of the peptide diversity of the Brotheas amazonicus venom. The chromatographic profiles and the mass compositions of the venom are provided. A total of 201 molecules were detected with molecular masses between 800 and 17000 Da. Eight peptides were de novo sequenced which did not present significative similarity with other known molecules. The molecules with masses between 6 and 7.5 KDa corresponded to approximately 8% of all detected molecules and molecules with masses between 2 and 7 KDa corresponded to 43%. Other molecules have masses ranging from 0.8 KDa to 2 KDa and 7 KDa to 17 KDa. This work shows that much has yet to be discovered regarding these animals and the composition of their venoms.